2018
DOI: 10.1038/s41385-018-0052-1
|View full text |Cite
|
Sign up to set email alerts
|

Notch ligand Delta-like 4 induces epigenetic regulation of Treg cell differentiation and function in viral infection

Abstract: Notch ligand Delta-like ligand 4 (DLL4) has been shown to regulate CD4 T-cell differentiation, including regulatory T cells (T). Epigenetic alterations, which include histone modifications, are critical in cell differentiation decisions. Recent genome-wide studies demonstrated that T have increased trimethylation on histone H3 at lysine 4 (H3K4me3) around the T master transcription factor, Foxp3 loci. Here we report that DLL4 dynamically increased H3K4 methylation around the Foxp3 locus that was dependent upon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 81 publications
0
14
0
1
Order By: Relevance
“…Notch signals are involved in the development and homeostasis of immune cells: JAG1-Notch, dLL4-Notch1 and dLL1-Notch2 signals promote the self-renewal of long-term hematopoietic stem cells, differentiation of early T-lymphocyte progenitors and differentiation of marginal zone B lymphocytes, respectively (133,134); dLL1/4 and JAG1/2 signals induce the differentiation of naïve T lymphocytes into Th1 and Th2 cells, respectively (135,136); dLL1 and JAG1 signals promote the differentiation of tumor-associated macrophages (TAMs) into M1-and M2-like phenotypes, respectively (137,138); dLL1 or JAG1 on MScs and JAG2 on hematopoietic progenitor cells induce the expansion of regulatory T (Treg) cells (139-141); and dLL4 on dendritic cells promotes Treg differentiation (142). By contrast, Notch-related immunological reprogramming in the tumor microenvironment may be more complex; scRNAseq revealed 20 subsets of T lymphocytes, including circulating Treg cells, non-cancerous tissue-infiltrating Treg cells and cancerous tissue-infiltrating Treg cells (143).…”
Section: Notch Signaling In the Tumor Microenvironmentmentioning
confidence: 99%
“…Notch signals are involved in the development and homeostasis of immune cells: JAG1-Notch, dLL4-Notch1 and dLL1-Notch2 signals promote the self-renewal of long-term hematopoietic stem cells, differentiation of early T-lymphocyte progenitors and differentiation of marginal zone B lymphocytes, respectively (133,134); dLL1/4 and JAG1/2 signals induce the differentiation of naïve T lymphocytes into Th1 and Th2 cells, respectively (135,136); dLL1 and JAG1 signals promote the differentiation of tumor-associated macrophages (TAMs) into M1-and M2-like phenotypes, respectively (137,138); dLL1 or JAG1 on MScs and JAG2 on hematopoietic progenitor cells induce the expansion of regulatory T (Treg) cells (139-141); and dLL4 on dendritic cells promotes Treg differentiation (142). By contrast, Notch-related immunological reprogramming in the tumor microenvironment may be more complex; scRNAseq revealed 20 subsets of T lymphocytes, including circulating Treg cells, non-cancerous tissue-infiltrating Treg cells and cancerous tissue-infiltrating Treg cells (143).…”
Section: Notch Signaling In the Tumor Microenvironmentmentioning
confidence: 99%
“…During the early differentiation stages of iTreg, the Notch and TGFβ pathways induce SMYD3 expression. During the early differentiation stages of iTreg, Notch signaling favors SMYD3 expression by RBP-Jκ direct recruitment to the SMYD3 promoter [33]. In addition, SMYD3 levels increase during 48 h of iTreg-skewing condition and TGFβ is the primary inducer of SMYD3, through the direct association of SMAD3 with the SMYD3 promoter [34].…”
Section: Smyd3 Levels Are Altered In Cancermentioning
confidence: 99%
“…Our in vitro data suggested that Jagged1 reduced the expression of Foxp3 at 10 nM concentration, while Delta-like 4 had no effect at this same concentration. Previous studies have indicated that Dll4 can increase Foxp3 expression 9,19 . These previous studies were performed using a 50 nM concentration of Dll4.…”
Section: Discussionmentioning
confidence: 98%